The impact of flexible working arrangement to the employees at Pejabat Setiausaha Kerajaan Negeri Kelantan (SUK) / Nurul Ayuni Shafei ... [et al.] - Shafei, Nurul Ayuni; Salleh, Nur Jalilah; Zainal Abidin, Nor Zaini (2021)
Nowadays, flexible working arrangement is one of the core concepts that is becoming important at the workplace. Many organizations provide the versatility at work to employees due to some circumstances such as COVID- 19 pandemic, the advancement of technology and a transition in the industrial system which have majorly changed the conventional working methods. The flexibility impacts both the employees and employers. In this paper, the relationship between FWA and the most dominant impacts of FWA is investigated.